Meta-analysis of the impact of postoperative complications on survival after oesophagectomy for cancer. Issue 5 (19th April 2018) - Booka, E; Takeuchi, H; Suda, K; Fukuda, K; Nakamura, R; Wada, N; Kawakubo, H; Kitagawa, Y
Abstract: Background: Oesophagectomy has a high risk of postoperative morbidity. The impact of postoperative complications on overall survival of oesophageal cancer remains unclear. This meta-analysis addressed the impact of complications on long-term survival following oesophagectomy. Methods: A search of PubMed and Cochrane Library databases was undertaken for systematic review of papers published between January 1995 and August 2016 that analysed the relation between postoperative complications and long-term survival. In the meta-analysis, data were pooled. The main outcome was overall survival (OS). Secondary endpoints included disease-free (DFS) and cancer-specific (CSS) survival. Results: A total of 357 citations was reviewed; 21 studies comprising 11 368 patients were included in the analyses. Overall, postoperative complications were associated with significantly decreased 5-year OS (hazard ratio (HR) 1·16, 95 per cent c.i. 1·06 to 1·26; P = 0·001) and 5-year CSS (HR 1·27, 1·09 to 1·47; P = 0·002). Pulmonary complications were associated with decreased 5-year OS (HR 1·37, 1·16 to 1·62; P < 0·001), CSS (HR 1·60, 1·35 to 1·89; P < 0·001) and 5-year DFS (HR 1·16, 1·00 to 1·33; P = 0·05). Patients with anastomotic leakage had significantly decreased 5-year OS (HR 1·20, 1·10 to 1·30; P < 0·001), 5-year CSS (HR 1·81, 1·11 to 2·95; P = 0·02) and 5-year DFS (HR 1·13, 1·02 to 1·25; P = 0·01). Conclusion: Postoperative complications after oesophagectomy, including pulmonary complications and anastomotic leakage, decreased long-term survival. Graphical Abstract: A systematic literature search retrieved 357 studies; of these, 21 studies evaluated the impact of postoperative oesophagectomy complications on long-term survival. In this meta-analysis, pulmonary complications and anastomotic leakage after oesophagectomy had a significant negative impact on overall (OS), cancer-specific (CSS) and disease-free (DFS) survival, and the postoesophagectomy complications had a negative impact on OS and CSS. Complications do influence survival in oesophageal cancer